OPTIMALISASI APLIKASI E-COMMERCE UNTUK PENJUALAN PADA TOKO DESFA BOGOR - Nur Azizah; Erna Astriyani; Listina Nadhia N (UNIVERSITAS RAHARJA, 2015)
In the current era of globalization, information technology drove rapidly. The computers are tools created to facilitate human work, currently in progress both in the manufacture of hardware and software. Shop Desfa desperately need once the existence of an information system to supportand provide satisfactory service for consumers. To which the author tries to make the final application of e-commrece sales in the muslim fashion store Desfa that is still using conventional means. At this time in the from Desfa shop selling Muslim clothing store alone. Sales of existing mechanisms to store Desfa that consumers can come directly and choose the clotes that will be bought. Aplication of e-commerce is the best solution for creating a scope broader sales and also to develop bussines sales. E-commerce is one of the appropriate means to promote existing products on store Desfa, by utilizing information System and the internet also can achieve a system that is higly effective and efficient in supporting the activities at this store.